THE ANALYSIS OF SIMILE IN TAYLOR SWIFT’S SONGS: - Tulung, Maria Rahelia; Maru, Mister Gidion; Kumayas, Tirza (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims at describing simile in Taylor Swift Songs. It is conducted to identify the types, the function and the contextual meaning of simile used in Taylor Swift’s Songs. In conducting this research, qualitative analysis is used. The data are analyzed through the steps of data reduction, data display, conclusion and verification as proposed by Miles & Huberman (2007). The instrument of collecting the data is the researchers themselves as the key instrument. The findings of this research show that there are two types of similes used in Taylor Swift’s Songs those are open and closed simile. Simile allows readers to relate the feelings of the author to their personal experiences. The similes are used to make the song more imaginable and meaningful. The most important function of simile is to draw sharp pictures in the mind through comparisons, to give deeper insight into things, person, and ideas trough suggestive association, or to explain abstract, complicated ideas in simple concrete imagery. It’s better to use as it should be so the people will not be offended but should make comfortable sense. In using simile, we need to consider with the situation and context. The contextual meaning is the meaning of the words according to the situation in which they are used.